Internal control of expenditure cycle PT DEF parts procurement - Myla Galuh Saumi; Tubagus Muhamad Yusuf Khudri (SEAN Institute, 2024)
This research aims to provide information to PT DEF regarding the results of the evaluation of internal control of spare parts procurement in accordance with the internal control framework published by COSO in 2013. PT DEF is a manufacturing company that has been established since 1993. The company has a spare parts inventory value which continues to increase by 12% every year from 2018 to 2023. This research is qualitative in nature using data collection methods of direct interviews with related parties, documentation studies, and direct observation of the expenditure cycle for spare parts procurement at PT DEF. The interviews used in this research were based on the Green Book internal control assessment which was adapted from the internal control framework published by COSO (2013) and interviews regarding the expenditure cycle and Fraud Triangle Theory were taken from the book by Romney and Steinbart (2021 ). From the results of the analysis and discussion of this research, it is concluded that internal control of spare parts procurement at PT DEF is not yet effective in the five components of the internal control framework published by COSO (2013), namely control environment, risk assessment, control activities, information and communication, and supervision activities. This causes many purchased spare parts to go unused and pile up in the company's warehouse. PT DEF requires activities to improve the expenditure cycle for spare parts procurement so that spare parts procurement activities run effectively.